2006
DOI: 10.1017/s0024282907006305
|View full text |Cite
|
Sign up to set email alerts
|

Populations of epiphytic lichens under stress conditions: survival strategies

Abstract: The effect of a copper-smelting plant on populations of Hypogymnia physodes and Tuckermanopsis sepincola was studied in the Middle Urals. A different population response was found between the two lichen species due to different life strategies. The pollution appears to decrease growth and developmental rate of H. physodes (a vegetatively reproducing strongly competitive species), resulting in a shift of population structure towards smaller, esorediate to low sorediate thalli. The background population of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
0
10
0
3
Order By: Relevance
“…Nevertheless, pollutants are relevant primarily at the southern limits of the boreal forest belt and in extrazonal montane conifer stands (Bruteig, 1993;Poikolainen et al, 1998). Furthermore, local pollution sources are widespread even in remote areas of North America, Scandinavia and Russia (Aamlid and Skogheim, 2001;Bjerke et al, 2006;Mikhailova, 2007).…”
Section: Air Pollutantsmentioning
confidence: 99%
“…Nevertheless, pollutants are relevant primarily at the southern limits of the boreal forest belt and in extrazonal montane conifer stands (Bruteig, 1993;Poikolainen et al, 1998). Furthermore, local pollution sources are widespread even in remote areas of North America, Scandinavia and Russia (Aamlid and Skogheim, 2001;Bjerke et al, 2006;Mikhailova, 2007).…”
Section: Air Pollutantsmentioning
confidence: 99%
“…Recently, Mikhailova (2007) studied survival strategies of epiphytic lichens growing close to a copper smelter in the Middle Urals. She investigated the responses of Hypogymnia physodes and Tuckermanopsis sepincola, as an asexually reproducing strong competitor, and a sexually reproducing weak competitor, respectively, and showed that T. sepincola benefits from the Cu-sensitivity of H. physodes.…”
Section: Lichens and Excess Heavy Metalsmentioning
confidence: 99%
“…Field studies demonstrated decreased production of apothecia, which are involved in sexual reproduction, and increased asexual reproduction by conidia (Nash and Gries 1995). Mikhailova (2007) found that Cu pollution caused growth abnormalities, distortion of apothecia and colour changes in thalli of Tuckermanopsis sepincola and decreased production of soredia in Hypogymnia physodes. Excess Mn caused ultrastructural damage and inhibited soredial growth in Hypogymnia physodes (Hauck and Paul 2005).…”
Section: Accumulation Of Heavy Metals By Lichensmentioning
confidence: 99%
“…Aside from morphological modifications, the colour change of thalli to a brownish or even dark brown tint was sometimes observed, especially in C. rei and C. conista. Such pigmentation is frequently explained by the increased content of heavy metals in the thalli and can also occur in other epigeic lichens [43,44].…”
Section: Early Epigeic Colonisersmentioning
confidence: 99%